2008
DOI: 10.1001/archderm.144.5.666
|View full text |Cite
|
Sign up to set email alerts
|

Looking Older

Abstract: Background-Skin appearance is a primary indicator of age. During the last decade, substantial progress has been made towards understanding underlying mechanisms of human skin aging. This understanding provides the basis for current use and new development of anti-aging treatments. Objective-To present state of the art knowledge pertaining to mechanisms involved in skin aging, with specific focus on the dermal collagen matrix. Results-A major feature of aged skin is fragmentation of the dermal collagen matrix. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
195
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 435 publications
(221 citation statements)
references
References 51 publications
4
195
0
2
Order By: Relevance
“…These enlarged fibroblasts produce increased levels of collagen and CTGF/CCN2. Interestingly, we recently reported that reduced fibroblast size/mechanical force also up‐regulates matrix metalloproteinase‐1 expression and thus causes collagen fibril fragmentation (Qin et al ., 2014), as observed in aged human skin in vivo (Fisher et al ., 2008, 2009). These data combined with our current findings provide a foundation for our understanding the cellular and molecular basis of age‐related loss of collagen production and increased collagen fragmentation in aged human skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These enlarged fibroblasts produce increased levels of collagen and CTGF/CCN2. Interestingly, we recently reported that reduced fibroblast size/mechanical force also up‐regulates matrix metalloproteinase‐1 expression and thus causes collagen fibril fragmentation (Qin et al ., 2014), as observed in aged human skin in vivo (Fisher et al ., 2008, 2009). These data combined with our current findings provide a foundation for our understanding the cellular and molecular basis of age‐related loss of collagen production and increased collagen fragmentation in aged human skin.…”
Section: Discussionmentioning
confidence: 99%
“…During aging, the dermal ECM undergoes progressive fragmentation that impairs fibroblast attachment with consequent reduction of size (Varani et al ., 2004; Fisher et al ., 2008, 2009; Quan et al ., 2013a). In aged skin, reduced size of fibroblasts is accompanied by their decreased production of key ECM components, such as type I collagen, fibronectin, and connective tissue growth factor (CTGF/CCN2) (Varani et al ., 2004, 2006; Fisher et al ., 2008; Quan et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this state, the ECM microenvironment is unable to provide sufficient mechanical stability to maintain normal cell spreading/mechanical force [7,20,27]. Therefore, age-related fragmentation of the collagen fibrils deleteriously alters fibroblast size/mechanical tension and function associated with skin connective tissue aging [7,27,28]. Reduced fibroblasts size stimulates intracellular ROS generation.…”
Section: Collagen Fragmentation Collapses Dermal Fibroblasts and Incrmentioning
confidence: 99%
“…At molecular levels, naturally aged and photoaged skin share common features of skin aging-thin and fragmented collagen [5]. Biochemical and histological studies have revealed that aged human skin is primarily characterized by a loss of collagen and damaged/disorganized collagen fibrils [6,7]. Alterations of the dermal connective tissue collagen impair the skin's structural and mechanical integrity, and eventually result in old-looking skin, such as thin, fragile, and wrinkled skin.…”
Section: Introductionmentioning
confidence: 99%